The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1086/427282
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Findings during Uncomplicated Acute Influenza in Ambulatory Adults

Abstract: Most ambulatory young adults with acute influenza have clinically insignificant abnormal electrocardiogram findings early during the illness. These abnormalities resolve promptly and are not associated with changes in cardiac markers or echocardiogram findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 24 publications
8
64
0
Order By: Relevance
“…Fever and cough were the most frequent symptoms in ILI patients. Fever was reported more often by H1N1 positive patients (91% vs. 72.9%; P < 0.01), with similar numbers found in literature, 87.3-95.9% [13,14,18,19]. Incidence of headache was also higher in H1N1 positive group (31.8% vs. 18.5%; P < 0.05).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Fever and cough were the most frequent symptoms in ILI patients. Fever was reported more often by H1N1 positive patients (91% vs. 72.9%; P < 0.01), with similar numbers found in literature, 87.3-95.9% [13,14,18,19]. Incidence of headache was also higher in H1N1 positive group (31.8% vs. 18.5%; P < 0.05).…”
Section: Discussionsupporting
confidence: 81%
“…History of drug allergies or asthma was more common in H1N1 positive patients; the same is reported by other researchers [4,19]. Other chronic pulmonary diseases (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Clinical findings in patients with influenza were consistent with typical systemic effects, such as high temperature, muscle pain and fatigue, and also indicated frequent episodes of myocardial ischemia (Greaves et al, 2003;Ison et al, 2005;Paul, 1963;Verel et al, 1976). These results led to the hypothesis that influenza may play a role in triggering cardiovascular events.…”
Section: Introductionmentioning
confidence: 62%
“…Typically, clinical manifestations are mild and result in uncomplicated cases, but there have been reports of fatal cases from cardiac involvement (8). ECG abnormalities can be seen in up to 45% of individual infected with influenza, including ST deviation, T wave flattening, Q wave formation, and atrial fibrillation (9). Observational studies have suggested that influenza viruses can trigger cardiovascular death and that vaccines against influenza may decrease the risk of cardiovascular events in susceptible individuals (10).…”
Section: Discussionmentioning
confidence: 99%